MyCera. Application of mycelial growth within digitally manufactured clay structures. (March 2022) - Jauk, Julian; Gosch, Lukas; Vašatko, Hana; Christian, Ingolf; Klaus, Anita; Stavric, Milena
In this paper we will demonstrate a digital workflow that includes a living material such as mycelium and makes the creation of structural designs possible. Our interdisciplinary research combines digital manufacturing with the use of mycelial growth, which enables fibre connections on a microscopic scale. We developed a structure that uses material informed toolpaths for paste-based extrusion, which are built on the foundation of experiments that compare material properties and growth observations. Subsequently, the tensile strength of 3D printed unfired clay elements was increased by using mycelium as an intelligently oriented fibre reinforcement. Assembling clay-mycelium composites in a living state allows force-transmitting connections within the structure. This composite has exhibited structural properties that open up the possibility of its implementation in the building industry. It allows the design and efficient manufacturing of lightweight ceramic constructions customised to this composite, which would not have been possible using conventional ceramics fabrication methods.